Implementasi Media Pembelajaran Interaktif Berbasis Animasi Dua Dimensi untuk Pogram Studi Desain Komunikasi Visual di SMK Bhakti Praja Margasari - Atiek Nurindriani; Aziz Azindani; Lailatul Fitri (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
Innovation is needed to make education more interesting and effective in the current era of computers and the internet. One of the efforts is to develop interactive learning media applications based on two-dimensional animation. This research aims to create and implement an interactive learning application based on 2D animation for the Visual Communication Desian study program at Bhakti Praja Margasari Vocational School, in order to increase student understanding and involvement. This study involves needs analysis, Desian, development and evaluation. A needs analysis is carried out to determine the learning materials and interactive features required. Applications were developed using animation and programming software, and evaluated to assess engagement and effectiveness. The research results showed that interactive learning media based on two-dimensional animation increased student interest and understanding. Students show higher motivation and are more engaged in learning. This application also helps teachers deliver lessons in a more interesting and interactive way. It is hoped that this application can help Bhakti Praja Margasari Vocational School students in learning Visual Communication Desian and can be used in other schools. This research also suggests further development, such as adding interactive features and improving animation.